2004
DOI: 10.1016/j.jcp.2003.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the accuracy of time-integration methods for the radiation–diffusion equations

Abstract: The governing equations for the radiation-diffusion approximation to radiative transport are a system of highly nonlinear, multiple time-scale, partial-differential equations. The numerical solution of these equations for very largescale simulations is most often carried out using semi-implicit linearization or operator-splitting techniques. These techniques do not fully converge the nonlinearities of the system so as to reduce the cost and complexity of the transient solution at each time step. For a given ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 23 publications
3
56
0
Order By: Relevance
“…However, the associated efficiency gain is not significant and the loss of accuracy might be problematic given the large range of timescales in a reacting flow simulation. Alternatively, the non-linear chemical source terms may be expanded using some type of low-order expansion [19][20][21]. However, it has been shown that these methods may be subject to severe time step size restrictions and stability issues when applied to combustion simulations [19], since they do not fully account for the non-linearity of the system [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the associated efficiency gain is not significant and the loss of accuracy might be problematic given the large range of timescales in a reacting flow simulation. Alternatively, the non-linear chemical source terms may be expanded using some type of low-order expansion [19][20][21]. However, it has been shown that these methods may be subject to severe time step size restrictions and stability issues when applied to combustion simulations [19], since they do not fully account for the non-linearity of the system [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some thoughts regarding time adaptation by these different methods and future endeavors necessary are discussed below. 4 …”
Section: Automated Time Step Controlmentioning
confidence: 99%
“…This test problem was previously introduced in [4]. Then, by assuming a particular solution for T (x), a suitable forcing function can be obtained by substituting in (9), a method more commonly known as the Method of Manufactured Solutions (MMS).…”
Section: Thermal Wave Problemmentioning
confidence: 99%
“…Indeed, procedures for time step selection often advise against reducing time steps far below the critical values for temporal stability [5, p. 510]. Nevertheless, small time steps are often necessary in practice, for example in problems of radiative transport [6] and fluid-structure interaction [7]. As the time step is reduced with a fixed mesh size, the deleterious effects of higher modes are inevitably admitted into the computation, even with algorithmic damping [8].…”
Section: Introductionmentioning
confidence: 99%